Manajemen Program Prakerin Dalam Meningkatkan Kompetensi Lulusan Sekolah Menengah Kejuruan - Septiana, Alma Damayanti (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
ABSTARCK Internship programs are urgently needed in an effort to improve the competence of graduates in vocational secondary education institutions. Competence of qualified vocational high school (SMK) graduates will not be achieved except through the implementation of an apprenticeship program. One of the competency standards for graduating from vocational high schools (SMK) is with apprenticeship. The purpose of internship is to provide graduates for students so that they have the skills and character they have in working according to the demands of a job. Good internships will produce graduates who are competent according to the work experience students have had. This study aims to analyze apprenticeship programs conducted by vocational secondary education institutions to improve students' graduation competence in vocational high schools (SMK). The results of this study indicate that vocational secondary education institutions already have good apprenticeship program planning and then implement the existing programs so that they have a positive impact and can be directly observed regarding increasing student graduation by having competencies according to their fields. Keyword: Manajement, Intership Program, Graduation Competency ABSTRAK Program prakerin sangatlah dibutuhkan dalam upaya meningkatkan kompetensi lulusan di lembaga pendidikan menengah kejuruan. Kompetensi lulusan sekolah menengah kejuruan (SMK) yang berkualitas tidak akan tercapai kecuali melalui pelaksanaan program prakerin. Salah satu standar kompetensi kelulusan sekolah menengah kejuruan (SMK) dengan prakerin. Tujuan prakerin ialah memberikan lulusan bagi siswa sehingga mempunyai keterampilan serta karakter yang dimiliki dalam bekerja sesuai dengan tuntutan di suatu pekerjaan. Prakerin yang baim akan menghasilkan lulusan yang berkompeten sesuai dengan pengalaman pekerjaan yang pernah dialami oleh siswa. Lokasi dari penelitian ini yakni SMK S Mahardika Karangploso Kabupaten Malang. Penelitian ini bertujuan untuk menganalisis program prakerin yang dilakukan oleh lembaga pendidikan menengah kejuruan untuk meningkatkan kompfetensi kelulusan siswa di sekolah menengah kejuruan (SMK). Hasil dari penelitian ini menunjukkan bahwa SMK S Mahardika Karangploso Kabupaten Malang telah memiliki perencanaan program prakerin yang baik dan kemudian mengimplementasikan program – program yang telah ada ditetapkan sehingga memiliki dampat positif dan dapat diamati secara langsung mengenai peningkatan kelulusan siswa dengan memiliki kompetensi sesuai dengan bidangnya. Kata Kunci: Manajemen, Program Prakerin, Kompetensi Lulusan